2022
DOI: 10.1080/01402390.2022.2038572
|View full text |Cite
|
Sign up to set email alerts
|

What is a military innovation and why it matters

Abstract: Levée en mass is standardized and nationalized compulsory military service. While popularly described as "invented" by a 1793 French law, there was a gap between the ideological claims of the 1793 levée en mass and reality. Making conscription work would require the reorientation of French industry, a strategy for dealing with desertion, and the establishment of new promotion patterns. The provision for a system of annual recruitment did not really come until the Jourdan law of 1798, when implementation of lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Finally, in light of the rapid pace of technological evolution, military ICT systems must be designed to incorporate new technologies and features. This approach to technological innovation is key to driving not only advancements in technology-based structures, but also in shaping more effective organizational structures and doctrinal principles in modern military strategy [107,108].…”
Section: Holistic Apporach For Cognitive Military Powermentioning
confidence: 99%
“…Finally, in light of the rapid pace of technological evolution, military ICT systems must be designed to incorporate new technologies and features. This approach to technological innovation is key to driving not only advancements in technology-based structures, but also in shaping more effective organizational structures and doctrinal principles in modern military strategy [107,108].…”
Section: Holistic Apporach For Cognitive Military Powermentioning
confidence: 99%
“…The importance of senior leadership engagement and support for the success of military innovation is well documented. 206 For example, in 2023, the Congressional Research Service identified it as a key barrier to Directed Energy Weapons development in the U.S. military. 207 These negotiations culminated in a full-scale collaborative engineering development MOU on 10 August 1986.…”
Section: Nulka Active Missile Decoymentioning
confidence: 99%
“…Aside from the fact that the current definition is a mix of technologies, products, systems, and capabilities (Bundesregierung 2020 , p. 3), the problem with a technology-driven approach to innovation is that it overlooks what technologies are expected to achieve. Truly innovative defense solutions only emerge when military end-users adopt and adapt to novel approaches thereby embedding technology in concepts, culture, organization, and operations (Borchert et al 2021 ; Horowitz and Pinyck 2022 ; Raska 2016 ). Therefore, innovation management should become more outcome and impact focused.…”
Section: Defense Industrial Policy For the Zeitenwendementioning
confidence: 99%